(untitled) (Strategic Policy and Diplomacy Review, 2026)
The United States has experienced profound political and socio-economic transformation since the non-consecutive election and inauguration of Donald Trump as its 47th President in 2025. Principal among these are sweeping alterations made to the overall immigration policy that have otherwise shaped entire diaspora communities whose members have sought higher education in the country. Measures such as restrictive immigration orders targeting specific countries, heightened visa scrutiny, federal pressure on higher education institutions, and even the detainment of foreign students have not only shaped the flow of migration into the United States but also resulted in a massive upheaval in the numbers of foreign scholars and in the procedures for assessing them. This essay analyses how said measures have affected student visa pathways within the broader geopolitical competition for international talent and student mobility, and how this has impacted the U.S.’ soft-power advantage in higher education.